Sistem Switch Monitoring Berbasis Web - Sandi Prasetyaningsih; Ahmad Kussyairi (Politeknik Negeri Batam, 2021)
IT Department as a part of IT network takes a role as a department which manages all networking and its facilities. All data related to networking is usually collected manually. This method emerges not only posibilities of redundancy data, but also losing data as result of improper design of database. Initially, this system aims for supporting the IT department to do documentation of switch and port to be more effective and efficient. To reach the purpose of this system, a waterfall method is used in which this method is used in which this method integrates with MySQL and PHP to create an output of pdf report.